Symbolization and domesticity in the Andean home: A phenomenological approach to dwelling in Coporaque, Peru - Gonzalo Ríos-Vizcarra; Luis Enrique Calatayud-Rosado; Aleixandre Brian Duche-Pérez (Frontiers of Architectural Research)
This study explores the symbolic value attributed by Indigenous inhabitants to their dwellings and how the physical structure of the home serves to align domestic activities with meanings related to their ancestral culture. To achieve this objective, we focused on the Peruvian Andes, specifically on Coporaque, an Indigenous village founded in the 16th century during colonial times. In this locality, qualitative research was carried out using the phenomenological approach, prioritizing the lived experience of the native inhabitants in their daily “life world” through in-depth interviews and direct observations. Our results broaden understanding of the Andean vernacular dwelling, making visible the ways in which the “Wasi” becomes a stage for the symbolic occurrence of domesticity. The results reveal several significant narratives on domesticity that support and give coherence to the life of these Indigenous communities, coinciding with the symbolic value that other cultures have attributed to dwellings. The study was able to conclude on the Indigenous house's function in sustaining regional identities and how its physical structure is embodied in the inhabitants until it becomes one of the last bastions of resistance against the homogenizing pressure that the globalized world tries to exert on native peoples.